The Editor’s Skill in Ensuring Text Perfection (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
As is known, editing text before printing is beneficial in all respects. This article describes the essence of text editing, the editor's activities and their role in improving the text, and the important aspects of these processes.